Análise da densidade mineral óssea: comparação entre idosas praticantes da modalidade de dança aeróbia e step e idosas fisicamente inativas - Velho, Rodrigo Baumann (2014)
This study analyzed bone mineral density (BMD) of older women who participated in Aerobic Dance and Bench Stepping Exercise Program (ADBS) and inactive women. Sample was composed by 44 women aged 65-75 years-old. The Modified Baecke Questionnaire for Older Adults was used to classified women as active or inactive. Participants who exercise in the Bench Stepping Exercise classes, three times per week, 60-min/session, in the last six months, were allocated in the active group (n=26), while who did not exercise were allocated in the inactive group (n=18). BMD was evaluated by Dual-Energy XRay Absorptiometry equipment, obtaining the Tscore for the following measurements of the femur: neck (FN), trochanter (FT), intertrochanteric (FI), and total (FT), and for the lumbar spine and total lumbar spine (L1, L2, L3, L4, and LT). Data were described by mean and standard deviation and differences between groups were analyzed by independent t-Test using the SPSS (p<0.05). Women in the IG were classified with osteopenia for femur (variation: -0.63 to -1.44) and lumbar spine (variation: -2.09 to -2.48). There was a condition closest to osteoporosis in the BMD-L3 (-2.48). Women in the AG showed a normal femur BMD (variation: -0.36 to -0.87), and the osteopenia was shown only in lumbar spine (variation: -1.30 to -1.79); however, these values were not accentuated as in the IG. The results confirmed the hypotheses of this study, which indicated that BS could be beneficial for BMD of older women. For this reason, it is suggest this exercise modality as an alternative strategy for attenuating the aging effects on bone mass, which consequently would provide beneficial effects on functional capacity and reducing the risk of falls, fractures and for development of the osteopenia and osteoporosis.